COVID-19 and food systems in Pacific Island Countries, Papua New Guinea, and Timor-Leste: Opportunities for actions towards the sustainable development goals. (June 2021) - Davila, Federico; Bourke, R.M.; McWilliam, Andrew; Crimp, Steven; Robins, Lisa; van Wensveen, Monica; Alders, Robyn G.; Butler, James R.A.
Abstract: Context: The COVID-19 pandemic has impacted global food systems. This has led to different strategies by communities, governments, and businesses involved in food systems to mitigate and adapt to the unfolding pandemic. Small Island Developing States are particularly exposed to the conflation of risks from COVID-19 disease, economic downturns, underlying climate vulnerabilities and biosecurity risks. Objective: Our study aimed to identify the food systems vulnerabilities, impacts, and opportunities for supporting resilience and sustainable development in selected Pacific Island countries, Papua New Guinea, and Timor-Leste. The study focused on the impacts from the first six months of the pandemic (February–July 2020), with remote data collection and analysis done between May and July 2020. Methods: We conducted 67 interviews, and triangulated information with desktop and news sources emerging at the time. We present results on the effect on smallholder livelihoods, supply chains, governance, communities and employment. Overall, the major impacts of COVID-19 have been on economies, posing risks to future food security and further hampering progress towards key Sustainable Development Goals. Results and conclusions: We found that unemployment and economic contraction have been the most severe effects to date, with long-term consequences for food value chains and smallholder farmers. Disruptions to tourism, labour migration, and remittances have led to varying socio-economic impacts throughout the region. Vulnerable groups, notably women, urban poor, and youth, have been disproportionately affected by unemployment. Timor-Leste has had some social protection measures, whereas in Pacific Countries these have been varied. The lockdowns and State of Emergency initially influenced the distribution and marketing of food, but local food economies are starting to stabilise. The continued functioning of international food supply chains reduced the risk of food insecurity in high import dependent nations, notably import dependent countries like Tuvalu and Kiribati. Significance: The results have significance for three recovery pathways. The first recovery pathway relates to revisiting value chains in light of restricted travel. The second recovery pathway exists through leveraging the adaptive capacities of communities to stimulate innovative agriculture that also integrates climate adaptation and nutrition. The third recovery pathway relates to addressing the structural challenges that perpetuate inequalities and poverty while finding new ways of implementing inclusive policies and research. Our study presents a set of comparative examples of managing a food system shock that can inform future systems-oriented research and policy for sustainable development. Graphical abstract: Unlabelled Image Highlights: We report on COVID-19 impacts on smallholders and value chains in Pacific Countries, Timor-Leste, and Papua New Guinea. We find that unemployment and economic contraction impacts have ramifications for smallholder livelihoods. Vulnerable groups have been disproportionately affected, there have been different policy and community responses. We present three recovery pathways to support future food systems. Pathways focus on: value chains, climate change and nutrition, and addressing structural inequalities.